Potential of imazaquin seed treatment for control of Stiga gesnerioides and Alectra vogeliii in cowpea (Viigna unguiculata) - Berner, D.K.; Awad, A.E.; Aigbokhan, E.I. (1994)
The herbicide imazaquin was tested for efficacy in striga gesnerioides and Alectra vogelii control when applied as a cowpea (Vigna unguiculata) seed treatment. Four sets of experiments were conducted in the laboratory and screenhouse. Two cowpea cultivar, three geographical isolates of S. gesnerioides from two hosts, and two geographical isolates of A. vogeli from two hosts were used. Preliminary experiments indicated cowpea seed treatments of 5-min duration in aqueous solutions of the ammonium salt of imazaquin, ranging from 1.8 to 7.2 mg a.i./ml, fit our test criteria of 50% germination and observable radical growth inhabitation. Treated cowpea seeds were dried and planted in soil-filled pots infested with 3,000 germinable S. gesnerioides or A. vogeli seeds. All experiments showed imazaquin seed treatments resulted in increased total cowpea dry weight in S. gesnerioides- infested pots in all experiments. Increases were significant at P<0.05 in two experiments. Observation in vitro, combined with screenhouse data, showed apparently normal parasite germination and attachment, indicating post attachment demise of both parasites. Increasing imazaquin rates led to delays in cowpea flowering; and increased soak times, at 3.6 mg a.i./ml and higher concentrations, led to reductions in cowpea seedling emergence. By prolonging seed soak times at an imazaquin concentration of 1.8 mg/ml, good parasite control was obtained. The lower rate at longer soak durations would provide both economical ($2.31 to $3.85 per hectare) control and the flexibility in treatment necessary for implementation on African farms. Field trials on farmer fields are under way to tailor specific seed treatment recommendations.